Numerical modelling for hydrodynamic simulation in archipelagic Southeast Asia: a case study from the southern tip of Malaysia using MIKE-21 - Jefri, Ikhmal Siddiq; Mokhtar, Mardiha; Razali, Muhammad Rizal; Jeofry, Muhammad Hafeez; Ramli, Muhammad Zahir; Miskon, Mohd Fuad; Mohamed, Juliana; Yunus, Kamaruzzaman (Institute of Physics Publishing, 2026)
Hydrodynamic modelling is commonly conducted with various numerical tools to analyse intricate coastal processes. These platforms facilitate efficient setups and enable detailed visualisations of current flows, wave behaviour, and the potential for overtopping. Although they demand significant input data and processing time, numerical modelling plays a crucial role, especially in data-deficient and physically demanding areas such as regions with numerous islands. This paper outlines a comprehensive numerical modelling approach utilizing the MIKE-21 Hydrodynamic module, which is tailored for coastal simulations in the archipelagic areas of Southeast Asia. The focus of the study is Johor, Malaysia, situated at the southern end of the region, where intricate shoreline dynamics and island arrangements affect current patterns and wave effects. Hydrodynamic simulations were conducted to examine current direction, velocity, and the potential for wave overtopping at eight selected coastal sites, utilising wind and wave data collected in 2024. The methodology is highlighted, covering aspects such as mesh creation, wind integration, bathymetric setup, and calibration of simulations. This paper offers a replicable modelling process for researchers and planners working in similarly intricate maritime settings. The findings reveal that the eastern coastline of Johor experiences greater wave energy and current flows than the western side, indicating a higher susceptibility to erosion and structural strain